PENINGKATAN KETERAMPILAN INTRUKSIONAL MELALUI PELATIHAN GURU MTS DALAM PEMAANFAATAN APLIKASI GAME CROSSWORDLABS - Maisyaroh Maisyaroh; Nurul Ulfatin; Mustiningsih Mustiningsih; Juharyanto Juharyanto; Nova Syafira Ariyanti; Maulana Amirul Adha; Wiwik Handayani (Yayasan Education and Social Center, 2023)
In the current era, innovation is really needed by teachers to optimize learning success, where they can utilize ICT and can organize game-based learning. The aim of this community service activity is to increase teacher creativity in learning and improve teacher skills in designing and implementing game-based learning in the classroom. In order to achieve the objectives of community service activities, a training approach is used, with four main stages, namely introduction, training, evaluation and providing feedback. The evaluation was carried out using a quantitative approach, using descriptive data analysis techniques and the Wilcoxon test. Based on evaluation and reflection on activities, it shows that teacher training was declared effective, there was an increase in teacher skills before and after the research was carried out. Teachers are also motivated to implement the material taught in the learning process